Marine heat flow data in the Guatemala basin, obtained during the GUATOPS project 2022/23 - Norbert Kaul (PANGAEA, 2025)
We measure subbottom temperature profiles at 66 new locations in the Guatemala Basin using MTL temperature sensors, mounted onto a gravity core barrel. Thermal conductivity values were measured on core material of 13 cores using a KD2 Pro needle probe. Heat flow values for 64 of the sites could be derived, showing a regime of very low geothermal heat flow, far below the expected values. there is a distinct boundary between low values north of 9°55 extquotesingleN and elevated values southward. The data were collected during research cruise JC228a, 13.-22. January 2023. The loction is offshore Costa Rica in the Pacific Ocean near 87°W, 10°N in the so called Guatemala Basin. Investigation of the subducting and bending oceanic plate, especially the cooling effect by circulating groundwater was one of the targets. A gravity corer of 6 m was equipped with 6 Miniaturized Temperature Logger (MTL). Vessel: James Cook on Cruise JF228a. The Project names are GUATOPS and GUATOPSheat for the heat flow survey.